ANALISIS FATWA DSN-MUI TENTANG PEDOMAN PENYELENGGARAAN RUMAH SAKIT SYARIAH - Mu'adil Faizin (Nizham Jurnal Studi Keislaman, 2018)
AbstractOn October 1, 2016, DSN-MUI issued the DSN-MUI Fatwa no. 107 / DSN-MUI / X / 2016 concerning Guidelines for the Implementation of Syariah Hospital. This fatwa is based on two reasons, namely the needs of society, and legal vacuum. It was found that the concept of sharia, which is being embodied by the National Sharia Council - The Indonesian Ulema Council (DSN-MUI) in this fatwa still uses a single point of view of the shari'a maqashid of Imam Syatibi, has not yet penetrated its development. Focused on the protection of individuals al-kuliyat al-khamsah, conical to the segmentation of Muslims an sich. Fikih products in the form of this fatwa actually implies the decline of Fikih Indonesia thinking. Considering the condition of the pluralistic Indonesian people should be responded by the development of Shariah thought to al-birr's attitude, oriented to humanity. The best service paradigm in various religious patients.Finally, Sharia attachment to the Hospital is not only limited to marketing methods or name adaptations, but also reflects Islam rahmatan lil a'lamin.